2006
DOI: 10.1111/j.1574-6968.2006.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis ofluxSinSerratia plymuthicaRVH1

Abstract: Autoinducer-2 (AI-2) is a signalling molecule proposed to act as a 'universal' signal for interspecies communication, regulating niche-specific genes with diverse functions in various bacteria. We have previously reported the production of AI-2 in strains from different Serratia species and recently, the luxS gene of two Serratia strains was isolated and shown to affect distinct phenotypes. In the current work, we have identified the luxS gene of Serratia plymuthica RVH1, and studied its effect on the N-acyl-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Our result that the strain with the plasmid-born luxS showed slower growth is in agreement with the observations of Van et al for Serratia plymuthica RVH1 [15] and Zhang et al for Edwardsiella tarda [16]. However, they all reported that overexpression of the luxS gene, which was accompanied by an increased production of AI-2, resulted in a slower growth [15, 16]. In contrast, these groups had not detected the level of pfs transcription in the overexpression strain.…”
Section: Resultssupporting
confidence: 94%
“…Our result that the strain with the plasmid-born luxS showed slower growth is in agreement with the observations of Van et al for Serratia plymuthica RVH1 [15] and Zhang et al for Edwardsiella tarda [16]. However, they all reported that overexpression of the luxS gene, which was accompanied by an increased production of AI-2, resulted in a slower growth [15, 16]. In contrast, these groups had not detected the level of pfs transcription in the overexpression strain.…”
Section: Resultssupporting
confidence: 94%
“…Thus, the observed growth pattern was not caused by an extracellular signal, but was likely of a metabolic, intracellular nature. This conclusion is strengthened by analogous results recently obtained using a similar approach in other luxS-positive bacteria, such as Staphylococcus aureus or Serratia plymuthica (Doherty et al 2006;Van Houdt et al 2006). An additional indication that, in Erwinia amylovora, luxS is involved in sulfur and amino acid metabolism is the position of the luxS open reading frame in the E. amylovora genome.…”
Section: Discussionsupporting
confidence: 64%
“…For S. plymuthica RVH1 knock‐out of luxS had no detectable effect on the AHL‐regulated phenotypes, nor on biofilm formation. However, overproduction of AI‐2 in RVH1 strains carrying luxS on a multicopy plasmid caused attenuated growth (Van Houdt et al ., 2006b). As the signal transduction pathway has not been identified, these results do not support a role in cell–cell communication for LuxS and AI‐2 in S. plymuthica RVH1, but rather suggest that the phenotypes associated with luxS knockout reported earlier in other Serratia spp.…”
Section: The Ai‐2 Moleculementioning
confidence: 99%